Pola Kepemimpinan Kepala Sekolah Perempuan di Sekolah Berbasis Islam - Rahman Afandi; Layla Mardliyah; Iis Sugiarti (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to describe the patterns of leadership of principals in Islamic-based schools, how principals manage time in carrying out their roles and efforts to unravel stereotypes. This research uses descriptive research method with a qualitative approach. The sample of this study is the principal, teachers, students and employees at the school. The results of the study illustrate, the leadership pattern applied by the Principal of MTs Al Hidayah Karangsuci Purwokerto is: 1) a transformational leadership pattern, a charisma shown through various approaches that embrace all parties with the aim of conditioning a better work situation; 2) Instructional and participatory leadership patterns, characterized by the principal's efforts to interact more with teachers, students, parents, colleagues, communities, more than men, support consensus decision-making, emphasize processes, encourage feelings of self-esteem, active participation, and share forces and information that help transform people's self-interest into organizational goals, influence teachers to use more desirable teaching methods in everyday life. In dismissing stereotypes, the principal has succeeded in creating a conducive climate in his institution so that all elements that are included in the academic climate of MTs can run well.